An An Investigation of Profit Growth in Indonesian Banking Before and During Pandemic Covid-19: Does Financial Performance Matter? - Ashari , Ardhita Pramesti; Simon , Zainal Zawir; Nasution, Ananta Hagabean; Zusryn , Alyta Shabrina; Asaari, Masagus (SAN Scientific, 2025)
This study examines the influence of Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Operational Income on Operating Costs (BOPO), and Loan to Deposit Ratio (LDR) on profit growth in the Indonesian banking sector, both before and during the COVID-19 pandemic. The research employs panel data regression with a sample of 44 banking companies listed on the Indonesia Stock Exchange (IDX). The results show that before the pandemic, CAR had a positive and significant effect on profit growth, while NIM and BOPO had negative and significant effects. LDR, however, showed a negative but insignificant effect. During the COVID-19 pandemic, CAR, NIM, and BOPO were found to have negative and significant impacts on profit growth, whereas LDR also negatively affected profit growth. Simultaneous testing confirms that CAR, NIM, BOPO, and LDR significantly influence profit growth in both periods. The findings provide managerial implications for banking companies to monitor key financial ratios that affect profitability. A healthier and more stable banking industry increases public trust and supports financial system stability. For investors, the study highlights the importance of understanding these financial factors when making investment decisions in the banking sector.